Developing agility and quickness - Dawes, Jay; Roozen, Mark 1961- (Sport performance series, 2012)
Contains more than 100 drills to improve sport-specific quickness and agility. This title focuses on improving athletes' fleetness of foot, speed of change of direction and reaction time. Applicable across almost every sport, it explains the purposes behind the training, presents tests to gauge ability and monitor progress